2015
DOI: 10.1038/hr.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of concentric left ventricular hypertrophy in patients with resistant hypertension: RESIST-POL study

Abstract: Left ventricular hypertrophy, especially concentric hypertrophy, has been shown to be an independent factor of cardiovascular diseases in patients with hypertension. Obstructive sleep apnea (OSA) and/or metabolic syndrome (MS) are common in patients with resistant hypertension (RHTN). The aim of this study was to evaluate factors associated with concentric hypertrophy in patients with RHTN. Data from 155 patients (92M, 63F) was analyzed. All patients underwent a thorough examination including: biochemical eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
2
3
0
3
Order By: Relevance
“…On multivariate regression analysis, patients with true RH in the current study were more likely to be black, and to have a higher mean BMI, medical history of DM requiring insulin, HFpEF, and CKD stage 3 or higher (Table ). These findings are consistent with those of prior studies conducted on RH subjects across all ranges of BMI values . DM and insulin resistance are associated with true RH, and this association is further amplified when DM is complicated with microvascular disease .…”
Section: Discussionsupporting
confidence: 91%
“…On multivariate regression analysis, patients with true RH in the current study were more likely to be black, and to have a higher mean BMI, medical history of DM requiring insulin, HFpEF, and CKD stage 3 or higher (Table ). These findings are consistent with those of prior studies conducted on RH subjects across all ranges of BMI values . DM and insulin resistance are associated with true RH, and this association is further amplified when DM is complicated with microvascular disease .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, two cross-sectional studies revealed that there was dose-effect relationship between the severity of OSA and the magnitude of BP increase, as well as the number of anti-hypertensive medicines used to manage hypertension. 39,40 In recent times, a clinical study revealed that clinically significant OSA was independently associated with concentric hypertrophy in patients with resistant hypertension, 41 which suggests that OSA might accelerate the adverse cardiovascular remodeling in subjects with resistant hypertension.…”
Section: Different Categories Of Hypertension Related To Osamentioning
confidence: 99%
“…Так, у пациентов с контролируемой АГ чаще формируется концентри-ческое ремоделирование миокарда ЛЖ, в то время как у пациентов с РАГ формируется концентрическая гипертрофия миокарда ЛЖ, несмотря на одинаковый стаж АГ, что, вероятно, связано с более интенсивным процессом развития гипертрофии и фиброза мио-карда ЛЖ [19], присущих для этой группы пациентов. Кроме того, перегрузка ЛЖ давлением, нарушения диастолической функции ЛЖ приводят к перегрузке ЛП и сопровождаются увеличением его размера, который у пациентов с РАГ стремится к предельным значениям, достижение которого увеличивает риск развития фибрилляции предсердий [20].…”
Section: Discussionunclassified